Why Do Students Prefer Augmented Reality: A Mixed-Method Study on Preschool Teacher Students' Perceptions on Self-Assessment AR Quizzes in Science Education - Angelos Sofianidis (MDPI AG, 2022)
Students' perceptions on AR applications have gained researchers' interest in the field of ICT-enhanced teaching and learning, especially in recent years. The current study investigates students' perceptions concerning their learning and immersive experiences gained using AR quizzes with formative self-assessment purposes in a science education university course during one semester. The research followed the mixed-method approach, and the data were collected sequentially by questionnaires and focus group discussions. A descriptive statistical analysis and a thematic analysis were conducted, respectively. Fifty-one (51) students participated in the quantitative data collection procedure and ten (10) of them participated in the focus groups. The results indicate that students are in favor of AR quizzes which justify their stance based on the learning gains and the immersive experiences. AR was underlined to play a significant role by creating an engaging environment of immersion. The findings support the positive stances of students over the combination of AR and formative self-assessment and highlight the role of immersion supported by AR technologies. Additionally, based on the relatively long period of application, the findings create doubts concerning the influence of the novelty effect on students' positive stances toward AR.